Mucus Sugar Content Shapes the Bacterial Community Structure in Thermally Stressed Acropora muricata - Lee, Sonny T. M.; Davy, Simon K.; Tang, Sen-Lin; Kench, Paul S. (Frontiers in Microbiology, 2016)
It has been proposed that the chemical composition of a coral’s mucus can influence the associated bacterial community. However, information on this topic is rare, and non-existent for corals that are under thermal stress. This study therefore compared the carbohydrate composition of mucus in the coral Acropora muricata when subjected to increasing thermal stress from 26°C to 31°C, and determined whether this composition correlated with any changes in the bacterial community. Results showed that, at lower temperatures, the main components of mucus were N-acetyl glucosamine and C6 sugars, but these constituted a significantly lower proportion of the mucus in thermally-stressed corals. The change in the mucus composition coincided with a shift from a γ-Proteobacteria- to a Verrucomicrobiae- and α-Proteobacteria-dominated community in the coral mucus. Bacteria in the class Cyanobacteria also started to become prominent in the mucus when the coral was thermally stressed. The increase in the relative abundance of the Verrucomicrobiae at higher temperature was strongly associated with a change in the proportion of fucose, glucose and mannose in the mucus. Increase in the relative abundance of α-Proteobacteria were associated with GalNAc and glucose, while the drop in relative abundance of γ-Proteobacteria at high temperature coincided with changes in fucose and mannose. Cyanobacteria were highly associated with arabinose and xylose. Changes in mucus composition and the bacterial community in the mucus layer occurred at 29°C, which were prior to visual signs of coral bleaching at 31°C. A compositional change in the coral mucus, induced by thermal stress could therefore be a key factor leading to a shift in the associated bacterial community. This, in turn, has the potential to impact the physiological function of the coral holobiont.